Acquisition of thermal field of spatial steel structure based on temperature measurements. (26th June 2019) - Lu, Wei; Huang, Kai; Teng, Jun
A spatial steel structure is a kind of high-order statically indeterminate structure, and the deformation caused by repeated changes in temperature will cause fatigue damage to its members. Therefore, for the design and safe use of spatial steel structures, it is of great significance to study the thermal effect. A method of acquiring the overall thermal field based on the limited temperature measurements is proposed in the paper. Firstly, the simulated thermal field of the structure is acquired by superposing the ambient temperature and solar radiation temperature. Secondly, the optimal mode for temperature estimations is determined by inverse distance weighted interpolation. Thirdly, the thermal field of the spatial steel structure is acquired based on the temperature measurements and the optimal mode. Finally, the feasibility of the proposed method is verified in the case of the large shell of the Zhuhai Opera House.